Efektivitas Kitosan sebagai Edible Coating Karkas Ayam Broiler - Ken Ratu Gharizah Alhuur; Eggy Muhammad Juniardi; Kusmayadi Suradi (Unpad Press, 2020)
The purpose of this study is to obtain the chitosan concentration which provides the most optimal effect on the quality of broiler chicken carcasses in terms of total bacterial counts, storability at room temperature storage (27-30℃) and carcass acceptability. The study was conducted experimentally with a completely randomized design, using four treatments and five repetitions. The trial was carried out by dipping the broiler chicken carcass into for levels of chitosan concentration, namely 0%, 1%, 2%, and 3% for three seconds and then drained for 10 minutes. The results showed that the chitosan solution with a concentration of 3% as edible coating on broiler chicken carcasses showed the best results in suppressing the number of bacteria (TPC = 47.38×106 CFU/g), and extending shelf life (1076,40 minutes), as well as acceptability is still preferred by the panelists.